Sclerotinia species in Serbia and possibilities of their control - Mihajlović, Milica; Hrustić, Jovana; Živanović, Maja; Petreš, Mladen; Pešić, Brankica (Pesticides and Phytomedicine / Pesticidi i fitomedicina, 2023)
Sclerotinia species are economically important, necrotrophic and aggressive plant pathogens with a broad host range and worldwide distribution. They act as airborne or soilborne pathogens, and can be transmitted by seed. These pathogens can affect crops both during the growing season and after harvest. Yield losses due to Sclerotinia diseases in susceptible crops vary and may be as high as 100%. The most common pathogen from the genus Sclerotinia in Serbia is S. sclerotiorum. It occurs regularly on sunflower and its incidence may exceed 50% in some years, thus causing economically important crop losses in Vojvodina. Recently, two new species were detected in Serbia: S. trifolium in alfalfa and S. minor in lettuce plants. Diseases caused by Sclerotinia spp. are difficult to control due to the long-term survival of sclerotia in the soil and development of airborne ascospores. As with many other diseases, there is no single treatment that can completely control these pathogens. Implementation of multiple strategies, such as cultural practices (sanitation, crop rotation and tillage), physical, chemical and biological protection, as well as deployment of resistant cultivars, is necessary for effective disease management.